Human energy consumption on oil palm harvesting process under different terrain: a case study / Mafuzah Malik - Malik, Mafuzah (Faculty of Plantation and Agrotechnology, 2017)
Energy is essential in order to improve production and productivity in agricultural sector. In plantation, the workers harvesting the oil palm on different terrain without knowing the energy that they have used to complete the task. Moreover, they do not know that inefficient usage of energy can lead to losses and increase the time of harvesting process in plantation. This case study aims to calculate the amount of human energy during harvesting process in oil palm plantation on flat and hilly area. This study was conducted at two plots of flat area and two plots of hilly area in oil palm plantation at Felcra Temeris. The data of field area, labor energy and time of harvesting was taken from July to September 2016. The result showed that the human energy at hilly area is higher than flat area with amount 12.50 MJHa-1 and 9.31MJHa-1 respectively. The time of harvesting at hilly area also longer than flat area which is 55.35 min/ha and 41.34 min/ha respectively. The difference in time for completing one hectare between flat and hilly area is 14.01 minutes. It can be concluded that the factor affecting human energy is topography and time of harvesting.